2004
DOI: 10.1111/j.1365-2133.2004.05705.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of a silk fabric in the treatment of atopic dermatitis

Abstract: The use of special silk clothes may be useful in the management of AD in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 12 publications
3
66
0
2
Order By: Relevance
“…Topical steroids and immunomodulators also appear to be able to reduce the degree of bacterial colonization [4,5,6], as does the recently proposed use of silver-coated textiles [7]. In a previous work with a special silk fabric (MICROAIR DermaSilk®) [8] we observed a clinical improvement of eczema in the area covered by the textile in 46 children with AD. This fabric also has antibacterial properties in vitro [9] thanks to a water-resistant treatment with AEGIS AEM 5572/5, a durable antimicrobial finish for textile products that prevents bacterial survival (including S. aureus ) and odour.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Topical steroids and immunomodulators also appear to be able to reduce the degree of bacterial colonization [4,5,6], as does the recently proposed use of silver-coated textiles [7]. In a previous work with a special silk fabric (MICROAIR DermaSilk®) [8] we observed a clinical improvement of eczema in the area covered by the textile in 46 children with AD. This fabric also has antibacterial properties in vitro [9] thanks to a water-resistant treatment with AEGIS AEM 5572/5, a durable antimicrobial finish for textile products that prevents bacterial survival (including S. aureus ) and odour.…”
Section: Introductionmentioning
confidence: 93%
“…In conclusion, the improvement seen in the eczema appears to be related to the direct contact with a delicate and soft fabric such as serine-free silk [8] which relieves itching, restores the disrupted cutaneous barrier and, thanks to the AEGIS coaction, protects the area from further overinfection.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that future material innovations will further improve compliance with compression therapy (30,31).…”
Section: Prospectsmentioning
confidence: 99%
“…Such a commercially available fabric (DermaSilk®) has antibacterial properties thanks to treatment with AEGIS AEM 5772/5, a covalently linked water-resistant antimicrobial finish for textiles based on the compound alkoxysilane quaternary ammonium [17]. In a recent trial, patients wearing DermaSilk showed significant clinical improvement of AD when compared to patients wearing cotton clothes [5, 18]. The aim of our study was to compare the effectiveness of DermaSilk with that of standard care consisting of the application of a modern topical corticosteroid and the wearing of cotton clothes in children suffering from moderate AD.…”
Section: Introductionmentioning
confidence: 99%